2010
DOI: 10.1103/physrevlett.105.135001
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Driven Fast Electron Collimation in Targets with Resistivity Boundary

Abstract: We demonstrate experimentally that the relativistic electron flow in a dense plasma can be efficiently confined and guided in targets exhibiting a high-resistivity-core-low-resistivity-cladding structure analogous to optical waveguides. The relativistic electron beam is shown to be confined to an area of the order of the core diameter (50 μm), which has the potential to substantially enhance the coupling efficiency of electrons to the compressed fusion fuel in the Fast Ignitor fusion in full-scale fusion exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…Robinson and Sherlock 17 proposed to apply a material having a higher resistivity core and lower resistivity cladding to induce an azimuthal magnetic field at the interface, which has been shown to be very effective for collimating fast electrons in recent experiments. 18,19 A concept of using a generator prepulse to produce a magnetic field that collimates the fast electrons injected into the target by the main pulse has also been proposed by Robinson et al 20 Recently, Sentoku et al 21 demonstrated that the fast electron propagation in metals can be controlled dynamically using ionization-driven resistive magnetic field by tuning the target ionization dynamics both in experiments and numerical particle-in-cell (PIC) simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson and Sherlock 17 proposed to apply a material having a higher resistivity core and lower resistivity cladding to induce an azimuthal magnetic field at the interface, which has been shown to be very effective for collimating fast electrons in recent experiments. 18,19 A concept of using a generator prepulse to produce a magnetic field that collimates the fast electrons injected into the target by the main pulse has also been proposed by Robinson et al 20 Recently, Sentoku et al 21 demonstrated that the fast electron propagation in metals can be controlled dynamically using ionization-driven resistive magnetic field by tuning the target ionization dynamics both in experiments and numerical particle-in-cell (PIC) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that, for compressed targets, beam hollowing is suppressed and the magnetic field increases with penetration depth of the fast electrons, suggesting that a high density background may lead to fast electron self-collimation. Fast electron propagation in targets preceded by different pedestal density and ramp profile is modeled by the 3D hybrid code ZEPH-YROS, 18,19 which treats the fast electrons kinetically using the Vlasov Fokker-Planck approach and the background plasma as a resistive fluid similarly to the code of Davies et al 26 The simulations show that collimated propagation of fast electrons can be enhanced in presence of an appropriate density profile.…”
Section: Introductionmentioning
confidence: 99%
“…Target structuring with different materials allows to obtain radially-convergent resistivity gradients. Such fields produced an observable collimation effect on REBtransport in both planar [22] and cylindrical [23] experimental designs. Numerical simulations explored the effect in even more complex cone-target structures [24][25][26].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…For any useful applications, it is therefore of great interest to find methods to weaken Weibel instabilities and increase the transport distance of intense fast electron beams in overdense plasma. Recently, many efforts in this direction have been reported [14][15][16][17]. Especially, in the work of [18], Mishra et al present an approach to achieve suppression/complete stabilization of the transverse electromagnetic beam Weibel instability by periodically modifying the electron density of background with an equilibrium density ripple, shorter than the skin depth.…”
Section: Introductionmentioning
confidence: 99%